Factors Affecting The Usage of E-filing for Individual Taxpayers - Suwito Suwito; Fitriani Sardju; Ruslee Nuh (Economics, Business, Accounting & Society Review, 2023)
This study aims to determine and analyze the influence of perception of usability, ease, security and confidentiality, information technology readiness, complexity, social factors, and taxpayer satisfaction on the use of e-filling. The population in this study is a Private Person Taxpayer registered with the Ternate Tax Service Office, North Maluku, Indonesia. The number of samples in this study was 392 Private Taxpayers. Sampling techniques use Convenience Sampling and data collection techniques through questionnaires. The data analysis method used is Partial Least Square with the Smart PLS statistics program. The results showed that perceptions of usability, security and confidentiality, information technology readiness, social factors, and taxpayer satisfaction affect the use of e-filling. In comparison, the perception of ease and complexity does not affect the use of e-filling.